P487 The feasibility of a digital platform for improving disease management among patients with Ulcerative Colitis. (27th May 2021) - Oddsson, S; Gunnarsdottir, T; Ylanne, K; Molander, P; Thorgeirsson, T
Abstract: Background: Ulcerative colitis is an idiopathic inflammatory condition of the colon and is the most common form of inflammatory bowel disease worldwide. It is a systemic disorder with no cure and therefore needs lifelong monitoring and management. This study's objective was to assess the feasibility and preliminary effectiveness of using a digital therapeutic intervention to improve disease management among patients with ulcerative colitis. Methods: Nine patients were recruited by the Finnish Crohn's and Colitis Patient Association to participate in a 4-week intervention via a digital platform (Sidekick Health). The primary outcomes included patient ratings of the platform and its therapeutic effects and patient reports of quality of life, physical activity, and medication adherence (on a scale from 0–10). Questionnaires were administered before and after the intervention. The study was conducted during the spring of 2019. Results: All nine participants completed the intervention (age-range=25–45, eight females and one male). Although not statistically significant, on average, all measures showed improvements from pre to post-intervention: quality of life improved for 7/9 participants (an average improvement of 10.3%), physical activity increased for 6/9 participants (an average of 3.3% increase). Also, medication adherence improved among 6/9 participants (improvement by 6.4% on average), supported by platform data indicating that 8/9 participants had used the platform medication reminders. In 86% of the daily reminders, they were acted upon and rewarded within the platform. Post-program, patients reported their experience of the program and when asked if they would recommend the program to others, the average score was 8.67 out of 10 possible. Also, 8/9 participants agreed or strongly agreed with the statement that the program had changed their health for the better. Conclusion: This small feasibility study suggests a digital therapeutic intervention is feasible and possibly an effective way to improve disease management among patients with ulcerative colitis. A more extensive study of this intervention is warranted.